The Health risks caused by heavy metals contamination of milk products - A W Abdul Mounam , Moutaz (Diyala Journal of Medicine, 2023)
Background: Nowadays, a lot of food products are produced in large quantities in factories. Milk and its derivatives are among the most important and well-known things that may be mentioned. Due to the industrialization of many nations, heavy metals are regarded as the most significant contaminants and have an impact on the presence of these substances in milk and dairy products. The toxicity of different heavy metals on human health, as well as their sources in milk and other dairy products are all represented in the current review paper, which focuses on methodologies and regulatory constraints for heavy metals in milk. The study also examines the frequency of heavy metals detected in milk samples from Iraq, a few other nations in Asia, South America, the United States, and Africa, as well as a few instances from Europe. strategies to lessen the number of heavy metals in milk and its products or stop them from contaminating such foods. Conclusion: Heavy metals have several health risks. Heavy metal exposure is especially prevalent in young age and the elderly due to milk drinking. Due to rapid industrialization and urbanization, law enforcement, and less restrictions, developing countries have high heavy metal levels in milk. Wealthy countries have less heavy metal pollution. Milk samples had significant lead and cadmium levels, requiring strict environmental and health protections.